PARALLEL PROGRAMMING IN PYTHON (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
Parallel programming in Python has become increasingly popular as it allows developers to leverage the power of modern hardware by executing multiple tasks simultaneously. This article provides an overview of parallel programming in Python, exploring its benefits, challenges, and best practices. We discuss key concepts such as multi-threading, multi-processing, and libraries such as concurrent.futures and multiprocessing, which enable parallelism in Python. Additionally, we highlight the growing relevance of parallel programming in the context of modern software development and the potential performance gains it offers.